2013
DOI: 10.1134/s1068162013030035
|View full text |Cite
|
Sign up to set email alerts
|

In vitro delivery of curcumin with cholesterol-based cationic liposomes

Abstract: A new cholesterol-based cationic lipid was synthesized; liposomes prepared on its basis were evaluated as drug delivery vehicles for curcumin. Free and liposome-encapsulated curcumin cytotoxicity against HeLa, A549, HepG2, K562 and 1301 cell lines was assessed. Liposomal curcumin with ED50 values ranging from 2.5-10 microM exhibited 2-8 times higher cytotoxicity than free curcumin. The synthetic cholesterol-based cationic lipid also enhanced cellular uptake of curcumin into tested cells. Cationic liposome alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Artificial membrane liposomes were prepared as previously reported [ 4 ]. A dry thin membrane of a mixture of phosphatidylcholine (PC) and cholesterol (CHL) or of a mixture of phosphatidylcholine (PC) and phosphatidylserine (PS) was prepared by evaporating a solution of the lipid and the polymer in methanol and by subsequent drying under a vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…Artificial membrane liposomes were prepared as previously reported [ 4 ]. A dry thin membrane of a mixture of phosphatidylcholine (PC) and cholesterol (CHL) or of a mixture of phosphatidylcholine (PC) and phosphatidylserine (PS) was prepared by evaporating a solution of the lipid and the polymer in methanol and by subsequent drying under a vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…This emerging propensity of nascent cancer cells for cholesterol uptake is an attractive target to use cholesterol as vehicle to increase the bioavailability of anticancer drugs. Thus, SuberAniloHydroxamic acid–cholesterol conjugates (SAHA–cholesterol) [ 11 ], cholesterol-based charged liposomes encaging doxorubicin [ 12 ] or curcumin [ 13 ] showed higher activity compared with the native drugs. Synthetic coumarin-caged cholesterol derivatives, for instance II , were triggered to release bioactive coumarines by photolysis at 350 nm [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…105 The median effective dose (ED 50 ) of βCD-C liposomes and free CUR was 2.9 μM and 1.5 μM, respectively. Apiratikul et al 106 synthesized CH-based cationic liposomes. ED 50 of CUR and liposomal CUR was 10 μM and 50 μM, respectively, which demonstrated that the cytotoxicity on A549 cells of liposomeencapsulated CUR had five times higher activity than that of free CUR.…”
Section: Liposomal Curcuminmentioning
confidence: 99%
“…In another study, CHbased cationic liposomes as drug delivery vehicles for CUR were synthesized. 106 Free and liposome-encapsulated CUR cytotoxicity against HepG2 cell line was assessed. The results showed that ED 50 values of the liposomes and free CUR were 4 μM and 30 μM, respectively.…”
Section: Liver Cancermentioning
confidence: 99%